Arsenic bioaccumulation and biotransformation in aquatic organisms - Wei Zhang; Ai-Jun Miao; Ning-Xin Wang; Chengjun Li; Jun Sha; Jianbo Jia; Daniel S. Alessi; Bing Yan; Yong Sik Ok (Environment International, 2022)
Arsenic exists universally in freshwater and marine environments, threatening the survival of aquatic organisms and human health. To elucidate arsenic bioaccumulation and biotransformation processes in aquatic organisms, this review evaluates the dissolved uptake, dietary assimilation, biotransformation, and elimination of arsenic in aquatic organisms and discusses the major factors influencing these processes. Environmental factors such as phosphorus concentration, pH, salinity, and dissolved organic matter influence arsenic absorption from aquatic systems, whereas ingestion rate, gut passage time, and gut environment affect the assimilation of arsenic from foodstuffs. Arsenic bioaccumulation and biotransformation mechanisms differ depending on specific arsenic species and the involved aquatic organism. Although some enzymes engaged in arsenic biotransformation are known, deciphering the complicated synthesis and degradation pathway of arsenobetaine remains a challenge. The elimination of arsenic involves many processes, such as fecal excretion, renal elimination, molting, and reproductive processes. This review facilitates our understanding of the environmental behavior and biological fate of arsenic and contributes to regulation of the environmental risk posed by arsenic pollution.